Artistic reporting in Ukrainian print and online media (features of genre development) - Shutiak, Lilia (WYDAWNICTWO UNIWERSYTETU RZESZOWSKIEGO, 2021)
The article examines the concept of literary reportage and the specificity of its functioning in Ukrainian printed and electronic media, with particular emphasis on the differences between traditional and literary reportage. The basis of literary reportage is informativeness (fact). As in the process of preparing traditional reportage, the journalist collects facts, interrogates witnesses, works with documents and archives, examines the situation and the characters of the future text. Analyticality manifests itself here in the understanding of the received information, methods of describing the problem and searching for its solutions, conducting observations both „from the inside” and „from the outside”.
Keywords: non-fiction; reportage; electronic media; information journalism; documentary studies